METTL3-Mediated m6A Methylation Regulates Muscle Stem Cells and Muscle Regeneration by Notch Signaling Pathway. (15th May 2021) - Liang, Yu; Han, Hui; Xiong, Qiuchan; Yang, Chunlong; Wang, Lu; Ma, Jieyi; Lin, Shuibin; Jiang, Yi-Zhou
Abstract : The Pax7+ muscle stem cells (MuSCs) are essential for skeletal muscle homeostasis and muscle regeneration upon injury, while the molecular mechanisms underlying muscle stem cell fate determination and muscle regeneration are still not fully understood. N6-methyladenosine (m 6 A) RNA modification is catalyzed by METTL3 and plays important functions in posttranscriptional gene expression regulation and various biological processes. Here, we generated muscle stem cell-specific METTL3 conditional knockout mouse model and revealed that METTL3 knockout in muscle stem cells significantly inhibits the proliferation of muscle stem cells and blocks the muscle regeneration after injury. Moreover, knockin of METTL3 in muscle stem cells promotes the muscle stem cell proliferation and muscle regeneration in vivo . Mechanistically, METTL3-m 6 A-YTHDF1 axis regulates the mRNA translation of Notch signaling pathway. Our data demonstrated the important in vivo physiological function of METTL3-mediated m 6 A modification in muscle stem cells and muscle regeneration, providing molecular basis for the therapy of stem cell-related muscle diseases.